Kerajaan Allah dalam Injil Matius - Selvia Selvia; Lelo Lelo; Defi Solestina; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The concept of the Kingdom of God in Matthew's Gospel is a central theme of the Teaching of Jesus Christ. The Kingdom of God can be understood as the reign of God that has entered this age through the presence of Jesus and will be perfect at His second coming. This research aims to understand the concept of the Kingdom of God in the Gospel of Matthew and its implications for the lives of believers. This research method uses textual and historical analysis to understand the concept of the Kingdom of God in the Gospel of Matthew. The results of the study show that the Kingdom of God has some very special characteristics, such as a government that is sinless and not weak before God, full of the Holy Spirit, and has great power to do extraordinary things.Jesus taught the concept of God's Kingdom through compelling parables and demonstrated important aspects of God's Kingdom. This research also shows that the coming of God's Kingdom refers to the second coming of Jesus, in which the Kingdom will be present in full power. Therefore, believers must be ready to receive the Kingdom of God in their lives and to demonstrate God's power in their actions.